A Prospective Comparative Study of Clinicoradiological Characteristics, Pulmonary Function, and Bronchodilator Response in Smokers and Nonsmokers with Chronic Obstructive Pulmonary Disease - K. Jisna; V. Jereen; A. Arthi; George Roshan Prasanth Durairaj; Dhinesh Kumar (Annals of African Medicine, 2026)
Abstract Introduction: Chronic obstructive pulmonary disease (COPD) is a heterogeneous condition with both smoking and nonsmoking etiologies. Data comparing clinicoradiological characteristics and bronchodilator response (BDR) between smokers and nonsmokers remain limited, mainly in low- and middle-income countries. Therefore, this investigation aimed to compare these parameters among smokers and nonsmokers with COPD. Methods: This hospital-based, prospective, comparative, cross-sectional study was conducted at a tertiary care center over 18 months. A total of 80 COPD patients (40 smokers and 40 nonsmokers) were enrolled. Baseline clinical, radiological, and spirometric data were recorded, and follow-up assessment was performed at 3 months. Pulmonary function testing was conducted according to the American Thoracic Society/European Respiratory Society guidelines. Data were analyzed by utilizing SPSS, with P < 0.05 considered statistically significant. Results: Baseline characteristics have been comparable among groups, except for gender distribution ( P < 0.001). Smokers had significantly higher respiratory rate and lower oxygen saturation ( P < 0.05). Hyperinflation was more common among smokers ( P < 0.05), whereas nonsmokers showed greater radiological improvement. Although baseline pulmonary function was similar, nonsmokers demonstrated significantly greater improvement in forced expiratory volume in 1 sec and higher bronchodilator responsiveness ( P < 0.05). Symptom burden was enhanced in both groups without a significant intergroup difference ( P > 0.05). Conclusion: Smokers with COPD exhibit greater physiological impairment and structural lung changes, whereas nonsmokers demonstrate better BDR and functional recovery. These findings highlight COPD heterogeneity and the need for phenotype-based management strategies .